30-Day Journey with St. Hildegard of Bingen - Sterringer, Shanon (Book collections on Project MUSE., 2019)
Enrich each day with wisdom from our greatest spiritual thinkers. Through brief daily readings and reflections, the 30-Day Journey series invites readers to be inspired and transformed. St. Hildegard of Bingen was a visionary mystic, a spiritual leader, and a woman ahead of her time. Whether you love St. Hildegard or are encountering her for the first time, this journey provides the perfect way to engage the thought of a compelling twelfth-century saint.